Kajian Biofisika FRRS Untuk Mengurangi Nyeri Kelelahan Pada Kaki Dengan Stimulasi Listrik dan Magnet - Primasari Cahya Wardhani; Nia Dwi Puspitasari; Zakiyah Dania Billah; Tri Anggono Prijo; Bagas Aryaseta; Sakinah Sakinah; Widya Rachma Wulan; Syahrul Munir (Universitas Andalas, 2024)
This research aims to design and test the effectiveness of the Foot Reflection-Relaxation Stimulator (FRRS), which combines electrical and magnetic stimulation as a reflexology therapy method to reduce pain caused by fatigue. FRRS is designed to stimulate reflex points in the feet by applying principles of physics such as static magnetic fields and Lorentz force, which are expected to enhance blood circulation and relax tense muscles. The testing was conducted on 25 healthy male participants who experienced leg fatigue after traveling a distance of 20 km. Pain levels were measured using the Numerical Rating Scale (NRS) before and after treatment with FRRS. The results showed a significant decrease in pain scale, from an average of 7 before treatment to 3.12 after treatment. The use of FRRS has proven effective in reducing pain due to fatigue in the legs, which is believed to be due to increased blood circulation and muscle relaxation. Thus, FRRS can be a practical and efficient solution to improve the quality of life for individuals who often experience fatigue and pain in their legs.